An Ordinance to Prevent the Use of Fire Arms, etc., § 1, Ordinances of the City of Hudson (1855). - (:unkn) unknown (General Publisher, 1855)
No person shall within this city carry any gun on lands not his own, without the written permission of the owner of legal possessor of such lands.
--
Keywords: CARRY